Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
8104911739
For Business Enquiry

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

if a x b = c x d and a x c= b x d, then prove that

Asked by 20th February 2009, 5:19 PM
Answered by Expert
Answer:

                  ax b = c x d ...(1)

                a x c= b x d...(2)

subtracting (1) from(2),

a x (b-c) =( c-b) x d

a x (b-c) +( b-c) x d=0

a x (b-c) - d x ( b-c) =0

(a-d) x (b-c)=0

Hence,|a-d|=0 or |b-c|=0
or (a-d) is parallel to (b-c).

Answered by Expert 22nd February 2009, 2:00 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp